QRS-T angle as a predictor of sudden cardiac death in a middle-aged general population - Aro, A. L.; Huikuri, H. V.; Tikkanen, J. T.; Junttila, M. J.; Rissanen, H. A.; Reunanen, A.; Anttonen, O. (Europace (London, England), 2012)
Spatial QRS-T angle measured from a 12-lead electrocardiogram (ECG) has been shown to predict cardiac mortality. However, there is a paucity of studies on the prognostic significance of frontal QRS-T angle, which is more readily available from the standard 12-lead ECG. The purpose of the present study was to investigate the importance of wide frontal QRS-T angle, QRS-axis, and T-wave axis as cardiac risk predictors in general population. We evaluated the 12-lead ECGs of 10 957 Finnish middle-aged subjects from the general population recorded between 1966 and 1972, and followed them for 30 ± 11 years. QRS-T angle 0 to 90°, QRS-axis -30 to 90°, and T-wave axis 0 to 90° were considered normal. The primary endpoint was death from arrhythmia, and the secondary endpoints were all-cause mortality and non-arrhythmic cardiac mortality. QRS-T angle ≥ 100° was present in 2.0% of the subjects, and it was associated with an increased risk of sudden arrhythmic death [relative risk (RR) 2.26; 95% confidence interval (CI) 1.59-3.21; P< 0.001) and all-cause mortality (RR 1.57; CI 1.34-1.84; P< 0.001), but not with non-arrhythmic cardiac mortality (RR 1.34; CI 0.93-1.92; P= 0.13). The prognostic significance of wide QRS-T angle was mainly due to abnormal T-wave axis, which predicted death from arrhythmia (RR 2.13; CI 1.63-2.79; P< 0.001), all-cause mortality (RR 1.39; 1.24-1.55; P< 0.001), and non-arrhythmic cardiac death (RR 1.87; CI 1.50-2.34; P< 0.001). Frontal QRS-T angle ≥ 100° increases the risk of arrhythmic death, this being mainly the result of an altered T-wave axis.